Dispersion over the business cycle: Passthrough, productivity, and demand - Mikael Carlsson; Alex Clymo; Knut-Eric Joslin (Sveriges Riksbank, 2022)
We characterize the dispersion of firm-level productivity and demand shocks using Swedish microdata including prices and utilization and analyse the consequences for firms and the aggregate economy. Demand dispersion increases by more than TFPQ dispersion in recessions. Productivity shocks pass through incompletely to prices and have limited effect on sales dispersion. Demand shocks explain most of the variation in sales dispersion. In a heterogeneousfirm model matching the micro facts, demand dispersion has unambiguously negative effects on output via a "wait and see" channel. Productivity dispersion does not generate "wait and see" effects, but affects output negatively by inducing markup dispersion.
Keywords: D21; D22; D81; E32; L11; 330; demand estimation; productivity; variable markups; business cycles; dispersion; uncertainty; passthrough; adjustment costs